2011
DOI: 10.1366/10-06037
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Surface Contamination and Self-Assembled Monolayers (SAMs) from Silver (Ag) Nanorod Substrates by Plasma Cleaning with Argon

Abstract: Surface contamination of surface-enhanced Raman (SERS)-active metallic substrates has been a limitation to the utility of SERS as an analytical technique, potentially affecting surface coverage, spectral reproducibility, and analytical limits of detection. We have developed a simple and versatile cleaning method for SERS-active Ag nanorod arrays that consists of a short (4 min) exposure of the substrate to an Ar(+) plasma in a low-pressure environment. The findings presented here demonstrate that this cleaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…[28,30] To remove the organic contaminants accumulated during fabrication and storage, before SERS measurements, the as-deposited AgNR substrates were cleaned for 2 min in a custom-built inductively coupled radio frequency plasma chamber, which was operated at 30 W under a constant flow of ultra-pure argon with a chamber pressure of~600 mTorr. [31] Bulk Raman spectra…”
Section: Density Function Theory (Dft) Calculationmentioning
confidence: 99%
“…[28,30] To remove the organic contaminants accumulated during fabrication and storage, before SERS measurements, the as-deposited AgNR substrates were cleaned for 2 min in a custom-built inductively coupled radio frequency plasma chamber, which was operated at 30 W under a constant flow of ultra-pure argon with a chamber pressure of~600 mTorr. [31] Bulk Raman spectra…”
Section: Density Function Theory (Dft) Calculationmentioning
confidence: 99%
“…A mild and efficient method has been reported for removing carbonaceous and organic contaminants from Ag nanorod arrays [52]. The results from this investigation demonstrated that under controlled plasma conditions and exposure times (<4 minutes), the Ar + plasma cleaning procedure essentially eliminated any detectable background organic and carbonaceous contamination from Ag nanorod substrates without substantially changing their morphology.…”
Section: Fabrication Characterization and Morphology Of Sers-activementioning
confidence: 87%
“…Moreover, the surface contaminants (or impurities) manifest themselves, even in very small concentrations, by their anomalous SERS bands that overlap the SERS signal of a studied molecule. Such problems were previously reported in the case of both colloidal NPs [12,13] and solid substrates [9,14,15]. Thus, special care must be exercised when analyzing any spectral pattern in an effort to reliably distinguish the bands coming from the analyte from those of the contaminants or, better still, to develop a method for preventing the contamination.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, special care must be exercised when analyzing any spectral pattern in an effort to reliably distinguish the bands coming from the analyte from those of the contaminants or, better still, to develop a method for preventing the contamination. There have been numerous ways to clean SERS-active surfaces from contaminants under ambient conditions, including electrochemical [9], plasma [14,15], or ozone cleaning [16], but none have been uniformly successful [11]. Unfortunately, a side result of some electrochemical desorption techniques can be the introduction of surface defects where the carbon contamination was present or strong oxidation due to the high chemical reactivity of Ag [16,17].…”
Section: Introductionmentioning
confidence: 99%